A sala de aula e a “cela” como espaços representativos das Políticas Públicas de Educação e de Socioeducação: uma abordagem a partir dos espaços vividos - Rodrigues, Rosemeri Terezinha Ferreira da Rocha (2010)
This research aimed to make them about the physical space as a school area lived in the past for teens (boys) in the inner center of Ponta Grossa Socioeducation who had the experience of dropping out of school, in the same city. And from the experiences reported to identify which elements work together to break with the academic institution; experience the strengths and weaknesses (as perceived by the subjects) experienced within the school. The methodological instruments used were: an open-ended questionnaire and interviews from the photographic images of the last schools in which the research subjects studied. The phenomena dropout / involved with the infraction was treated as a metaphor "route margin and spaces classroom / cell were used in the real and symbolic dimension to the discussion of Public Policy Education and socioeducation. To characterize the route classroom - cell analysis was performed in documentary productions scientific reports and investigations of national and international agencies as the Getúlio Vargas Foundation (FGV), UNESCO and UNICEF also worked the space-time history of policies for children and adolescents in Brazil (in the national, state and municipal) to the current situation which exists in the Statute for Children and Adolescents (1990). The research methodology chosen was orientated towards the articulation of different levels categorized as methodological poles and the theoretical constructed from two epistemological: phenomenology (as support for the interviews in the field) and the dialectic in the construction and analysis of the research object. The results of this investigation followed three parallel paths: a survey of socioeconomic characteristics and school history of the research subjects, comparing the results of this investigation with other listed throughout the study and classification of accounts from the interviews in groups based on thematic similarities that indicate relevant the discussion. These themes were not defined a priori but emerged from the speech of the research subjects. The main results presented from the analysis showed that the factors that influence the disruption of school life of adolescents were strong geographical mobility (lack of housing), households with only one charge (most headed by women) for the provision of income play functions that offer low pay or no income, low parental education, lack of opportunities for cultural enrichment and little variation in the opportunities to develop physical skills (lack of incentive programs to sports, culture and leisure) lack of inclusion of non-formal education, easy access to drugs in the school environment, low self-esteem, teen pregnancy (early parenthood), and use of coercive measures in school (expulsion). The themes discussed from the reports submitted were fighting in front of schools, attendance at bars and other places of commerce, easy access to drugs in the school environment, violent games and fights within the school and vulnerabilities positive evidence of autonomy and role the experiences within the school.